EFFECT OF PHOSPHORUS FERTILIZER ON GROWTH, YIELD ANDFIBRE QUALITY OF TWO COTTON CULTIVARS - Makhdum, Muhammad Iqbal; Malik, Muhammad Nawaz A.; Shabab-ud-Din; Chaudhry, Fazal Illahi (Journal of Research (Science), 2025)
Studies were carried out on cotton cultivars varying in plant structure to find their responses to phosphorus fertilizer at Central Cotton Research Institute, Multan. The treatments consisted of two cotton cultivars (CIM-240 and MNH-147) and three phosphorus doses (0,50 and 100 kg P2O5 ha-1) and were arranged in split plot design with four replications. The results showed significant increase in seed cotton yield due to phosphorus fertilizer application. Cultivar CIM-240 was more responsive to phosphorus fertilization than that of MNH-147.